Perceived Ease of Use, Usefulness, and Risk on Actual E-wallet Usage Through Intention Among FISIP Students - Putri Salsa Ajzahrah; Annisa Wahyuni Arsyad; Wira Bharata; Rosyid Nurrohman (Jurnal Manajemen, 2026)
The rapid growth of the digital economy has transformed consumer behavior, especially in adopting financial technologies such as e-wallets. This study examines the influence of perceived ease of use, perceived usefulness, and perceived risk on actual e-wallet usage through behavioral intention among students of the Faculty of Social and Political Sciences, Mulawarman University. The Technology Acceptance Model (TAM) is employed as the theoretical foundation, integrating perceived risk as an external variable to explain behavioral variations. A quantitative approach using Structural Equation Modeling–Partial Least Square (SEM–PLS) with SmartPLS 4 was applied. The sample consisted of 100 respondents, determined through Slovin’s formula with a 10% margin of error. Data were collected using a structured questionnaire with a five-point Likert scale. The results show that perceived ease of use (t = 4.744; p = 0.000) and perceived usefulness (t = 3.392; p = 0.001) significantly and positively affect behavioral intention, while perceived risk (t = 1.915; p = 0.056) has a negative but insignificant effect. Behavioral intention significantly affects actual use (t = 5.187; p = 0.000), confirming its mediating role. However, the direct effects of ease, usefulness, and risk on actual use are insignificant. The study reaffirms TAM’s relevance and suggests including moderating factors such as trust or digital literacy. Practically, e-wallet providers should improve usability, clarify benefits, and strengthen security to encourage continued use.